Layer‐Stacking Growth and Electrical Transport of Hierarchical Graphene Architectures. (11th February 2014) - Luo, Birong; Chen, Bingyan; Meng, Lan; Geng, Dechao; Liu, Hongtao; Xu, Jie; Zhang, Zhiyong; Zhang, Hantang; Peng, Lianmao; He, Lin; Hu, Wenping; Liu, Yunqi; et al.
<x xml:space="preserve">Abstract</x> Hierarchical graphene architectures (HGAs) that grow by stacking of layers are produced on a liquid copper surface using chemical vapor deposition. The stacking mode — for example hexagonal–hexagonal–hexagonal or hexagonal–snowflake–dendritic — can be simply controlled. Measurements of the electrical properties of HGAs indicate that hierarchical stacking of graphene may be a simple and effective way of tailoring their properties without degrading them. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>